Model Pemesanan Bahan Baku menggunakan Peramalan Time Series dengan CB Predictor - Pujadi, Tri (Bina Nusantara University, 2014)
A company that manufactures finished goods often faces a shortage of raw materials, due to the determination of the quantity of raw material ordering improper because it is done by intuition and the lack of raw material inventory reserves. This resulted in costs because inefficient production processes are inhibited or had to perform an emergency procurement of raw materials to meet customer orders. The company seeks to use the method in determining the order quantity of raw material, comprising the steps of (1) collecting historical data of raw material use, step (2) forecasting needs raw materials, step (3) calculating the order quantity forecasting based on the data by comparing the deterministic method and probabilistic methods. Calculating safety stock for each raw material is done so as to cope with the situation outside of normal conditions, such a surge in orders. In its design, the system will be developed using the Unified Modeling Language modeling language (UML) on the basis of the concept of object-oriented analysis and design (Object Oriented Analysis and Design). With the proposed implementation of the information system, the company can estimate the need for raw materials more quickly and accurately, and can determine the order quantity that is tailored to the needs. So that the costs associated with ordering and storage of raw materials can be minimized.